Directional Topography Influences Adipose Mesenchymal Stromal Cell Plasticity: Prospects for Tissue Engineering and Fibrosis - Gabriel Romero Liguori; Qihui Zhou; Tácia Tavares Aquinas Liguori; Guilherme Garcia Barros; Philipp Till Kühn; Luiz Felipe Pinho Moreira; Patrick van Rijn; Martin C. Harmsen (Stem Cells International)
Introduction. Progenitor cells cultured on biomaterials with optimal physical-topographical properties respond with alignment and differentiation. Stromal cells from connective tissue can adversely differentiate to profibrotic myofibroblasts or favorably to smooth muscle cells (SMC). We hypothesized that myogenic differentiation of adipose tissue-derived stromal cells (ASC) depends on gradient directional topographic features. Methods. Polydimethylsiloxane (PDMS) samples with nanometer and micrometer directional topography gradients (wavelength w=464-10, 990 nm; amplitude a=49-3, 425 nm) were fabricated. ASC were cultured on patterned PDMS and stimulated with TGF-β1 to induce myogenic differentiation. Cellular alignment and adhesion were assessed by immunofluorescence microscopy after 24 h. After seven days, myogenic differentiation was examined by immunofluorescence microscopy, gene expression, and immunoblotting. Results. Cell alignment occurred on topographies larger than w=1758 nm/a=630 nm. The number and total area of focal adhesions per cell were reduced on topographies from w=562 nm/a=96 nm to w=3919 nm/a=1430 nm. Focal adhesion alignment was increased on topographies larger than w=731 nm/a=146 nm. Less myogenic differentiation of ASC occurred on topographies smaller than w=784 nm/a=209 nm. Conclusion. ASC adherence, alignment, and differentiation are directed by topographical cues. Our evidence highlights a minimal topographic environment required to facilitate the development of aligned and differentiated cell layers from ASC. These data suggest that nanotopography may be a novel tool for inhibiting fibrosis.